2005
DOI: 10.1002/hed.20246
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of longitudinal serum cytokine and angiogenesis factor levels as markers of therapeutic response and survival in patients with head and neck squamous cell carcinoma

Abstract: Longitudinal changes in serum HGF, IL-6, IL-8, and VEGF were detected with treatment response, relapse, or complications in individual patients and were associated with survival, with HGF showing the strongest relationship with survival. HGF, IL-6, IL-8, and VEGF merit investigation as markers of response, survival, and recurrence in larger prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
69
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 32 publications
9
69
1
1
Order By: Relevance
“…This appeared to represent a process of ''recovery'' towards pre-treatment levels, taking place as soon as chemo-irradiation was stopped. We could find only two relevant studies in the literature [9,10]; both were limited to sVEGF, and their conclusions were in disagreement with ours. However, we suggest that both of them might have inadvertently missed the process of increment in sVEGF levels during that interval, because of their different study design.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…This appeared to represent a process of ''recovery'' towards pre-treatment levels, taking place as soon as chemo-irradiation was stopped. We could find only two relevant studies in the literature [9,10]; both were limited to sVEGF, and their conclusions were in disagreement with ours. However, we suggest that both of them might have inadvertently missed the process of increment in sVEGF levels during that interval, because of their different study design.…”
Section: Discussioncontrasting
confidence: 76%
“…In that study, 18/25 patients were treated with three cycles of chemotherapy. Each cycle involved five days of continuous infusion of paclitaxel, and was administered every three weeks along the course of irradiation [10].…”
mentioning
confidence: 99%
“…In addition we demonstrated a higher level of expression in many of the angiogenic factors in both the tumour tissue and the associated nodal tissue, compared with tissue from the healthy control group, which is in accordance with previous studies where angiogenic factor levels of MMP-9 (24), HGF, VEGF (21,25) and IL-8 (22) were increased in patients with HNSCC compared with the control group (21). In contrast to the angiogenesis-related proteins, which increased with tumour progression, angiogenin and TIMP1 were found to decrease with disease progression.…”
Section: Discussionsupporting
confidence: 92%
“…In addition we have shown that there is increased expression of some of these factors in the normal mucosa adjacent to the tumour compared with both the metastatic nodal tissue and uvula control tissue, suggesting that the processes may be occurring in a wider area than just the main tumour mass, potentially predisposing the patient to recurrence or the development of a second primary tumour supporting the 'field of cancerization' hypothesis. The angiogenic growth factors VEGF, IL-8, bFGF, HGF are commonly found to be overexpressed in HNSCC in lysates (8) and systemically (21,22). In the current study 32 of the 40 angiogenesis-related proteins analysed had an increasing expression in the tumour tissue with advancement of the tumour stage.…”
Section: Discussionmentioning
confidence: 99%
“…However, in accordance with the present findings, no positive correlation was observed between tissue TIMP-1 positivity or serum TIMP-1 levels and disease stage or tumour grade. Druzgal et al (29) reported that the serum levels of IL-6, IL-8, hepatocyte growth factor and VEGF were increased in patients with HNSCC as compared to the normal control group. However, no association was observed between IL-8 levels and tumour stage in the present study or between tumour and metastatic nodes.…”
Section: Discussionmentioning
confidence: 99%